2022
DOI: 10.3390/pharmaceutics14071346
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Affinity Purification of Adeno-Associated Virus Using Periodic Counter-Current Chromatography

Abstract: Replacing batch unit operations of biopharmaceuticals by continuous manufacturing is a maturing concept, with periodic counter-current chromatography (PCC) favoured to replace batch chromatography. Continuous affinity capture of adeno-associated virus (AAV) using PCC has the potential to cope with the high doses required for AAV therapies thanks to its inherent high throughput. The implementation of continuous AAV affinity capture using a four-column PCC process is described herein. First, elution buffer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The presence of several charged groups in its structure (positively charged amines and negatively charged C-terminal carboxylic acid) could be the explanation for the good performance of arginine across the different affinity ligands [ 46 ]. This strategy has also been applied to other viral vectors; for instance, in the purification of adeno-associated viruses [ 47 ]. The effect of the pH on viral release was also investigated for the selected buffer.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of several charged groups in its structure (positively charged amines and negatively charged C-terminal carboxylic acid) could be the explanation for the good performance of arginine across the different affinity ligands [ 46 ]. This strategy has also been applied to other viral vectors; for instance, in the purification of adeno-associated viruses [ 47 ]. The effect of the pH on viral release was also investigated for the selected buffer.…”
Section: Resultsmentioning
confidence: 99%
“…The nanofiber adsorbents reveal a good dynamic binding capacity and recovery yields even at low residence times in comparison to packed beds. Mendes et al, using periodic counter-current chromatography, reported an AAVs recovery of 82.8% using Capto AVB™ of 0.2 mL, with 10-fold higher residence times in comparison to the used nanofibers ( Mendes et al, 2022 ). With respect to the experimental binding capacity, the highest value (6.08 × 10 14 TP mL −1 ) was obtained for a residence time of 4.8 s. Although capacity is in the same order of magnitude as what is reported by some manufacturers there is a substantial improvement in diminished residence times Cytiva, 2018 ; Cytiva, 2020a ; Fisher Scientific, 2017 ; Repligen Corporation, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, dedicated systems for Level 1 process intensification are beginning to gain traction, both due to the diversity of systems offered and user familiarity to concepts such as continuous chromatography, simulated moving bed, and so forth (Baur et al, 2016; Girard et al, 2015). While these sorts of systems have been typically limited to protein‐based therapies, recent work has been done using intensified systems for advanced therapies (Mendes, Bergman, et al, 2022). However, most of the work published in the literature today has been done by academic groups, and the translation into GMP processes is still to be seen.…”
Section: Choosing a Process Intensification Scheme For A Processmentioning
confidence: 99%